REVITALISASI KELEMBAGAAN PETANI SEBAGAI WAHANA ALIH TEKNOLOGI DAN INKUBATOR BISNIS PENDUKUNG AGRO TECHNO-PARK PORWOSARI, SEMARANG - Soesilowati, Etty; Martuti, Nana Kariada Tri; Sumastuti, Efriyani; Setiawan, Avi Budi (Jurnal Graha Pengabdian, 2020)
Abstrak: Beberapa tahun terakhir Dinas Pertanian berusaha memanfaatkan lahan eks di Kelurahan Purwosari Kecamatan Mijenmenjadi Taman Teknologi Pertanian atau â€œAgro Techno-Parkâ€ (ATP). Tujuannya adalah untuk memperkuat ekonomi kerakyatan berbasis keunggulan lokal dan membangun iklim usaha yang inovatif, kreatif dan kondusif. Permasalahan umum yang dihadapi antara lain ialah lemahnya sistem kelembagaan di tingkat petani, keterbatasan Sumber Daya Manusia pengelola ATP, kurangnya infrastruktur pendukung, belum ada UMKM yang bergerak di bidang jasa & pengolahan, serta belum adanya payung hokum/instrument kebijakan yang mendukung keberadaan ATP. Berdasarkan permasalahan mitra yang ada, maka dilakukan kegiatan pengelolaan dan pengembangan sumberdaya manusia, komoditas, dan sistem kelembagaan petani dan optimalisasi fungsi ATP melalui metode Sekolah Lapang, Agrowisata, Pelatihan dan Inkubasi bisnis, serta membangun Business Partnership hulu hilir Agroindustri. Kegiatan Pengabdian kepada Masyarakat ini menghasilkan KUB â€œSekar Taniâ€ yang beranggotakan Kelompok Wanita Tani, teknologi pengolahan produk olahan buah, Eduwisata, serta pembangunan Pasar Buah. Hasil evaluasi menunjukan bahwa wanita tani mampu menghasilkan sirup buah, selai, manisan, sari buah, tepung buah, keripik, dan kue kering. Teknologi pengolahan menjadikan buah tahan lama, memperpanjang umur simpannya dan meningkatkan pendapatan keluarga petani.Abstract: In the last few years the Department of Agriculture has tried to use the former land in Purwosari Village, Mijen District to become an Agricultural Technology Park or "Agro Techno-Park" (ATP). The aim is to strengthen the people's economy based on local excellence and to build an innovative, creative and conducive business climate. Common problems faced include the weak institutional system at the farmer level, limited Human Resources for ATP managers, lack of supporting infrastructure, no MSMEs engaged in services & processing, and the absence of legal umbrella / policy instruments that support the existence of ATP. Based on the problems of existing partners, management and development activities of human resources, commodities, and farmer institutional systems are carried out and optimization of ATP functions through the Field School method. Agro-tourism, training and business incubation, as well as building a Business Partnership upstream and downstream of Agro-industry. This Community Service activity resulted in the KUB "Sekar Tani" which consists of the Women Farmers Group, technology for processing fruit processed products, education, and the construction of a Fruit Market. The results of the evaluation showed that female farmers were able to produce fruit syrup, jam, sweets, fruit juice, fruit flour, chips, and pastries. Processing technology makes the fruit durable, extends its shelf life and increases the income of family farmers. as well as the development of the Fruit Market. The results of the evaluation showed that female farmers were able to produce fruit syrup, jam, sweets, fruit juice, fruit flour, chips, and pastries. Processing technology makes the fruit durable, extends its shelf life and increases the income of family farmers. as well as the development of the Fruit Market. The results of the evaluation showed that female farmers were able to produce fruit syrup, jam, sweets, fruit juice, fruit flour, chips, and pastries. Processing technology makes the fruit durable, extends its shelf life and increases the income of family farmers.